Investigating Repurchase Intention Through Perceived Value and Pricing Sensitivity - Ismatullah, Azka Dani; Handrito, Radityo Putro (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2025)
The increasing competition in the digital game store industry, driven by technological advancements, encourages companies to develop effective marketing strategies by first understanding the factors that influence user loyalty. This explanatory quantitative study aims to analyze and explain the effect of perceived value on repurchase intention among digital game store users in Indonesia, with price sensitivity as a moderating variable. The sample was selected using a non-probability sampling method with purposive sampling technique, acquiring 222 respondents. The respondents were users of Steam and/or Epic Games Store, residing in Indonesia, aged at least 18 years, and had made purchases through these platforms. The data were analyzed through hierarchical regression analysis using IBM SPSS version 26. The results show that perceived value has a positive and significant effect on repurchase intention. However, price sensitivity does not significantly affect repurchase intention, and it does not moderate the effect of perceived value on repurchase intention.